Benzoylation of polyphenylene oxide: characterization and gas permeability investigations - Bhole, Yogesh S.; Kharul, Ulhas K.; Somani, S. P.; Kumbharkar, S. C. (European Polymer Journal, 2005)
Benzoylation of polyphenylene oxide (PPO) was carried out with aromatic acid chlorides bearing specific groups at para-position (H methyl, Br, Cl and nitro), which differ in their polarity and bulk. The reaction conditions were optimized individually to get the high degree of substitution. These materials were characterized for thermal as well as other physical properties that are known to affect the gas permeation. In a series investigated, the nitrobenzoyl substitution on PPO resulted in the highest increase in glass transition temperature and the lowest thermal stability. An estimation of the packing density parameters-fractional free volume by density measurement and the d-spacing by X-ray diffraction analysis showed an increase in the packing density. The gas permeability was found to decrease in all the cases of benzoylation. The helium and oxygen based selectivities were increased, while CO2 based selectivities were decreased. The unusual trend observed in the gas permeation properties is explained on the basis of nature of substituent and the degree of substitution. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: benzoylation; Gas permeability; polyphenylene oxide; selectivity

Enhancement of gas permeation properties of polybenzimidazoles by systematic structure architecture - Kumbharkar, Santosh C.; Karadkar, Prasad B.; Kharul, Ulhas K. (Journal of Membrane Science, 2006)
Systematic structural variations in thermally stable polybenzimidazole (PBI) are explored that led to a substantial improvement in gas permeation properties. Physical property determinations revealed that incorporation of hexafluoroisopropylidene and tert-butyl groups led to amorphous polymers with slightly lowered thermal stability and decreased chain packing. PBI based on 4,4'-(hexafluoroisopropylidene)bis(benzoic acid) and 5-tert-butyl isophthalic acid exhibited 10-40 times higher permeability, while changes in selectivities for industrially important pairs ranged from modest decrease of 75% or less than that of PBI based on isophthalic acid. The O-2/N-2 selectivity was almost doubled in case of PBI based on 5-tert-butyl isophthalic acid. Gas diffusion coefficients were estimated from solubility and permeability coefficient determinations. These, along with dual-mode sorption parameters estimated from sorption isotherms provided an insight towards variations in permeation behavior. The permeability predictions for heavier gases in isophthalic acid based PBI correlated well with physical properties. The occurrence of permeation characteristics (especially P-H2 and P-H2/P-N2) near Robeson's upper bound, high thermal stability and good solvent solubility achieved by these structural modifications depicted the potential of this family of polymers as gas separation membrane materials. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Diffusion; Gas permeation; Polybenzimidazole; Sorption; thermal stability

Surface modification of polyacrylonitrile based ultrafiltration membrane - Lohokare, Harshada R.; Kumbharkar, S. C.; Bhole, Yogesh S.; Kharul, Ulhas K. (Journal of Applied Polymer Science, 2006)
Ultrafiltration membrane based on polyacrylonitrile prepared by phase inversion method using zinc chloride as an additive showed more than 90% rejection for BSA and 90-110 Im(-2) h(-1) water flux. The surface modification of this membrane was studied using ethanolamine, triethylamine, sodium hydroxide, and potassium hydroxide solutions. The effect of base treatment time and temperature on water flux and rejection was investigated. The membranes exhibited swelling by NaOH treatment followed by deswelling by HCl post-treatment, similar to pH responsive membranes. The treatment by organic as well as inorganic bases improved water flux with a slight lowering in BSA rejection by dead-end mode type treatment. A 230% increase in water flux was achieved by sodium hydroxide treatment in crossflow mode without a noticeable pore swelling by SEM. The contact angle of the modified membranes was decreased as compared to the unmodified one indicating appreciable surface modification. As the treatment time or temperature increased, the ESCA analysis showed increased population of Na-carboxylate groups. (c) 2006 Wiley Periodicals, Inc.
Keywords: BSA rejection; chemical treatment; polyacrylonitrile membrane; surface modification; Ultrafiltration

Assessing feasibility of polyarylate-clay nanocomposites towards improvement of gas selectivity - Bhole, Yogesh S.; Wanjale, Santosh D.; Kharul, Ulhas K.; Jog, Jyoti Prakash (Journal of Membrane Science, 2007)
Polymer-clay nanocomposites are well known to reduce the penetrant permeability by following tortuous path. Effects of such reduction in gas permeability on variation in selectivity of nanocomposites prepared using a high permeability polymer were examined. The polyarylate: poly (tetramethyl bisphenolA-iso/terephthalate) that exhibits high permeability and moderate selectivity was chosen for making nanocomposites with two organically modified clays (Cloisite 6A and 10A) by solution intercalation method. The nanocomposite formation for various clay loadings (3, 5 and 7% w/w) in polyarylate was ascertained by change in physical properties (X-ray diffraction, DMA, TEM). Behavior of solution viscosity and nanocomposite density indicated existence of polymer-clay layer interactions. As anticipated, though the gas permeability of pure gases, viz., He, N-2, CH4 and CO2 exhibited decrease, it was not monotonous. This decrease was more for larger gases (N-2, CH4 and CO2) in comparison to the decrease for smaller gas (He) permeability. This led to a decrease in CO2/N-2 and CO2/CH4 selectivities and increase in He/CO2 selectivity; while He/CH4 selectivity was increased substantially at 7% clay loading. This variation indicated feasibility of nanocomposites formation as a tool for improving selectivity of certain gas pairs. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Gas permeation; Nanocomposites; polyarylates; selectivity; solution intercalation

Effect of substituent polarity, bulk, and substitution site toward enhancing gas permeation in dibromohexafluorobisphenol-A based polyarylates - Ishole, Yogesh S.; Karadkar, Prasad R.; Kharul, Ulhas K. (Journal of Polymer Science Part B-Polymer Physics, 2007)
The gas permeation properties of polyarylates were tuned by varying nature and site of substituents present on both of its monomers, viz., bisphenol and dicarboxylic acid. The phenyl rings of hexafluorobisphenol-A were substituted in asymmetric manner by polar bromine to obtain dibromohexafluorobisphenol-A. This bisphenol was polymerized with equimolar mixture of iso- and terephthalic acid (base case), bromo- and nitroterephthalic acid (polar group substituted acids), 4,4'-hexafluoroisopropylidene bis(benzoic acid), and t-butyl isophthalic acid (bulky group containing acids). Physical properties and gas permeation properties of these polyarylates were investigated to assess combined effects of asymmetric nature of bisphenol substitution, polar nature of substituent bromine, hexafluoroisopropylidene group present at the bridge position of bisphenol, and substituent present on the acid moiety. The combination of these substituent types led these polyarylates to lie near Robeson upper bound. The gas sorption analysis and estimation of diffusivity in these polyarylates shed a light on observed variations in gas permeation properties by attempted structural variations. (c) 2007 Wiley Periodicals, Inc.
Keywords: asymmetric substitution; Diffusion; Gas permeation; gas sorption; polyarylates; selectivity; structure-property relations

Gas permeation in amine functionalized silicon rubber membranes - Achalpurkar, Manoj P.; Kharul, Ulhas K.; Lohokare, Harshada R.; Karadkar, Prasad B. (Separation and Purification Technology, 2007)
Silicon rubber (SR) based thin film composite (TFC) membranes find increasing applicability in various industrial separations owing to its excellent thermal and chemical stability. The functionalization of SR would provide enhanced separation characteristics for certain separation applications. The present research focuses on gas permeation properties of dense and thin film composite membranes based on amine substituted silicon rubber (ASR) and unsubstituted silicon rubber (SR). The dense membrane sorption analysis indicated that presence of amine functionality in ASR increased pressure dependant CO2 sorption capacity. Owing to this, an elevation Of CO2 permeability by 15% and CO2 based selectivities by 22-34% in comparison to that of unsubstituted SR was observed. The TFC membranes with SR and ASR as the selective layer on the top of different ultrafiltration (UF) supports with varying properties based on polyacrylonitrile and polysulfone were prepared. The effects of crucial parameters that affected TFC membrane performance, viz., coating solution concentration, UF support membrane porosity and nature of materials were investigated. The preparation of ASR based TFC membranes was demonstrated with a simple crosslinking agent-glutaraldehyde while analyzing effects of crosslinking time on their permeation properties. Polyacrylonitrile (PAN) was found to be better support layer material for ASR based TFC formation than polysulfone (PSF). Thin defect free coating layer can be obtained by appropriate combination of coating solution concentration and support UF membrane porosity. The analysis of effective skin layer thickness of TFC membranes indicated that careful optimization of these parameters is necessary to achieve defect free TFC membranes possessing a good combination of permeance and selectivity. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Carbon dioxide; Gas permeation; silicon rubber; thin film composite membrane

Gas sorption and transport in polyarylates: effect of substituent symmetry and polarity - Karadkar, Prasad B.; Kharul, Ulhas K.; Bhole, Yogesh S.; Badhe, Yogesh P.; Tambe, Sanjeev S.; Kulkarni, Bhaskar D. (Journal of Membrane Science, 2007)
The gas sorption properties of polyarylates based on bisphenol-A possessing symmetric/asymmetric substitution by nonpolar -CH3 group and symmetrically linked terephthalic acid were examined. The effects of substitution of polar bromine on terephalic acid moiety of polyarylate based on asymmetrically substituted bisphenol were also studied for physical, sorption and transport properties. The estimation of dual mode sorption parameters, solubility and diffusion coefficient revealed that nature of the substituent and substitution type plays a crucial role in depicting permeation properties. An asymmetric substitution by -CH3 group increased solubility coefficient of pure gases (N-2, O-2, CH4 and CO2) up to 27% and symmetric substitution increased the same up to 106%. This was coupled with 7-35% increase in solubility selectivity in both cases of substitution, which ascertained the usefulness of methyl group substitution in polyarylates based on terephalic acid. The pressure dependency of solubility coefficients and solubility selectivity was also investigated for these polyarylates. The sorption and transport properties of these polyarylates correlated well with physical properties of polyarylates and gases studied. The sorption/desorption kinetics of symmetrically substituted TMBisA-T was performed in order to deduce time dependent sorption behavior and to evaluate diffusivity coefficient. The apparent diffusion coefficients from sorption kinetics, desorption kinetics and from steady-states permeation-sorption were compared. The diffusion coefficients of CH4 and N-2 deduced by these methods correlated well with each other. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Diffusion; kinetics; permeation; polyarylates; Sorption

Nitration and amination of polyphenylene oxide: synthesis, gas sorption and permeation analysis - Bhole, Yogesh S.; Karadkar, Prasad B.; Kharul, Ulhas K. (European Polymer Journal, 2007)
A high degree of nitration of polyphenylene oxide (PPO) was successfully achieved by carefully optimizing synthetic protocol. The reduction of nitro group to amino could be done quantitatively. The physical properties of formed polymers were investigated and correlated with gas sorption and permeation properties. The formed polymers were amorphous in nature as revealed by wide angle X-ray diffraction spectra. An increase in the packing density in comparison to unsubstituted PPO as a result of induced polarity was indicated by lowering of fractional free volume and d-spacing. The substitution by either nitro or amino group increased the chain stiffness as revealed by the dynamic mechanical analysis. Though both, nitro and amino group substitution on PPO led to a decrease in pure gas permeability, the selectivity of various gas pairs was increased by these substitutions. The gas sorption analysis revealed that both, solubility selectivity and diffusivity selectivity were increased by these polar group substitutions. The nitro group substitution was more effective in improving solubility selectivity, while amino group substitution was more effective in improving diffusivity selectivity. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Amination; nitration; permeation; polyphenylene oxide; Sorption

2(7-3) fractional factorial optimization of polybenzimidazole based membrane electrode assemblies for H-2/O-2 fuel cells - Kannan, Ramaiyan; Islam, Md. Nazrul; Rathod, D.; Vijay, M.; Kharul, Ulhas K.; Ghosh, P. C.; Vijayamohanan, K. (Journal of Applied Electrochemistry, 2008)
We describe the usefulness of a statistical fractional factorial design to obtain consistent and reproducible behavior of a membrane-electrode-assembly (MEA) based on a phosphoric acid (PA) doped polybenzimidazole (PBI) membrane, which allows a H-2/O-2 fuel cell to operate above 150 degrees C. Different parameters involved during the MEA fabrication including the catalyst loading, amount of binder, processing conditions like temperature and compaction load and also the amount of carbon in the gas diffusion layers (GDL) have been systematically varied according to a 2(7-3) fractional factorial design and the data thus obtained have been analyzed using Yates's algorithm. The mean effects estimated in this way suggest the crucial role played by carbon loading in the gas diffusion layer, hot compaction temperature and the binder to catalyst ratio in the catalyst layer for enabling continuous performance. These statistically designed electrodes provide a maximum current density and power density of 1,800 mA cm(-2) and 280 mW cm(-2), respectively, at 160 degrees C using hydrogen and oxygen under ambient pressure.
Keywords: Carbon loading; Fractional factorial optimization; MEA; PBI; PEMFC

Effective arsenic removal using polyacrylonitrile-based ultrafiltration (UF) membrane - Lohokare, Harshada R.; Muthu, M. R.; Agarwal, Gopal P.; Kharul, Ulhas K. (Journal of Membrane Science, 2008)
Applicability of polyacrylonitrile (PAN)-based negatively charged ultrafiltration (UF) membrane for effective arsenic removal has been demonstrated, to our knowledge, for the first time. The hydrolysis of PAN-based UF membrane surface by NaOH leading to the formation of carboxylate (-COO-) groups and reduction in initial pore size rendered As-V rejection capability by Donnan exclusion principle. A lowering in pore size was indicated by the reduction in water flux and elevation in rejection of protein and polyethylene glycol (PEG). NaOH treatment leading to formation of carboxylate group on the membrane surface was indicated by FTIR-ATR, while contact angle measurement indicated increased hydrophilicity. This treatment rendered membrane surface smoothening as confirmed by SEM and AFM analyses. The molecular weight cut off after the NaOH treatment was found to be similar to 6 kDa. The rejection of pentavalent arsenic (As-V) by these surface modified membranes was studied with different feed concentration, cross-flow velocity, pressure, temperature and pH. Experiments with 50 ppb As-V in feed showed that arsenic rejection was close to 100% and remained constant up to 6 h. Feed sample concentration of 1000 ppb and 50 ppm of As-V showed >95% rejection at pH 7 and room temperature, but for 1000 ppm feed concentration, the rejection was 40-65%. For concentrations <= 50 ppm of arsenic in the feed, the rejection coefficient was not dependent on cross-flow velocity or transmembrame pressure. The rejection for 1000 ppm. concentration of As-V varied from 40 to 65% with variation in the cross-flow velocity and transmembrane pressure as the concentration polarization was important. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Arsenic rejection; concentration polarization; cross-flow velocity; Polyacrylonitrile; surface modification; Ultrafiltration

Synthesis, characterization, and gas permeability of aromatic polyimides containing pendant phenoxy group - Kothawade, Sandeep S.; Kulkarni, Mahesh P.; Kharul, Ulhas K.; Patil, Anandrao S.; Vernekar, Subhash P. (Journal of Applied Polymer Science, 2008)
A diamine containing a pendant phenoxy group, 1-phenoxy-2,4-diaminobenzene, was synthesized and condensed with different aromatic dianhydrides [4,4'-oxydiphthalic dianhydride, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 3,3',4,4-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracorboxylic dianhydride, and pyromellitic dianhydride] by one-step synthesis at a high temperature in m-cresol to obtain polyimides in high yields. Most of the polyimides exhibited good solvent solubility and could be readily dissolved in chloroform, sym-tetrachloroethane, N,N-dimethylformamide, NN-dimethylacetamide, and nitrobenzene. Their inherent viscosities were in the range of 0.33-1.16 dL/g. Wide-angle X-ray spectra revealed that these polymers were amorphous in nature. All these polyimides were thermally stable, having initial decomposition temperatures above 500 degrees C and glass-transition temperatures in the range of 248-281 degrees C. The gas permeability of 4,4'-oxydiphthalic dianhydride and 4,4'-(hexafluoroisopropylidene)diphthalic anhydride based polyimides was investigated with pure gases: He, H-2, O-2, Ar, N-2, CH4, and CO2. A polyimide containing a -C(CF3)(2)- linkage showed a good combination of permeability and selectivity. (C) 2008 Wiley Periodicals, Inc.
Keywords: Gas permeation; membranes; polyimides; selectivity; structure-property relations

Design of an "allsolid-state'' supercapacitor based on phosphoric acid doped polybenzimidazole (PBI) electrolyte - Rathod, Dhanraj; Vijay, Meenu; Islam, Md. Nazrul; Kannan, Ramaiyan; Kharul, Ulhas K.; Kurungot, Sreekumar; Pillai, Vijayamohanan (Journal of Applied Electrochemistry, 2009)
The effectiveness of phosphoric acid doped polybenzimidazole as a polymer electrolyte membrane to fabricate an all solid-state super capacitor has been explored using hydrous RuO(2)/carbon composite electrodes (20 wt.%) of surface area 250 m(2) g(-1) with many intrinsic advantages. The electrochemical evaluation of these super capacitors through cyclic voltammetry, charge/discharge and impedance measurements demonstrate the utility of this type of thin, compact and flexible supercapacitor capable of functioning at 150 degrees C to yield a maximum capacitance of about 290 F g(-1) along with a life of more than 1,000 cycles. A power density of 300 W kg(-1) and energy density of 10 Wh kg(-1) have been accomplished although the equivalent series resistance (ESR) of about 3.7 Omega needs to be reduced further for high rated applications.
Keywords: Electrochemical characterization; Electrochemical supercapacitor; Energy storage device; PBI electrolyte; RuO(2)/carbon composite

N-substitution of polybenzimidazoles: synthesis and evaluation of physical properties - Kumbharkar, Santosh C.; Kharul, Ulhas K. (European Polymer Journal, 2009)
Series of N-substituted polybenzimidazoles (PBI) were synthesized using selective alkyl groups with varying bulk and flexibility, viz., methyl, n-butyl, methylene trimethylsilane and 4-tert-butylbenzyl. PBl-I based on 3,3'-diaminobenzidine (DAB) and isophthalic acid and PBI-Bul based on DAB and 5-tert-butyl isophthalic acid were chosen for N-substitution. Structural characterizations of substituted polymers by FT-IR and (1)H NMR revealed elimination of hydrogen bonding. Evaluation of their physical properties revealed that N-substitution rendered better solvent solubility in common organic solvents, more open polymer matrix, but reduced thermal properties in comparison to their respective parent PBI. 4-tert-butylbenzyl, methylene trimethylsilane or n-butyl group substituted polymers were soluble even in chlorinated solvents (CHCl(3) and TCE). Substantial variations in gas permeability of inert gases, He and Ar and attractive P(He)/P(Ar) selectivity, especially after methyl group substitution depicted potential of these materials for gas separation. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Gas permeation; hydrogen bonding; N-Substitution; Polybenzimidazole

Selective synthesis of cumene by isopropylation of benzene using catalytic membrane reactor - Bokade, Vijay V.; Kharul, Ulhas K. (Chemical Engineering Journal, 2009)
Selective isopropylation of benzene to cumene is demonstrated using catalytic membrane reactor (CMR), to our knowledge for the first time and the performance was evaluated against conventional plug flow reactor (PFR). Almost complete elimination of byproducts like polyalkylated benzene and higher aromatics could be made possible by using CMR. These are present in significant amount when reaction is carried out with PFR. The cumene selectivity increased up to a maximum of 97.25% by CMR as against 90.05% with conventional PFR. The effect of reaction parameters that can greatly influence the process economics, such as liquid hourly space velocity (LHSV), reactant mole ratio and catalyst/reactor volume ratio were investigated. Changes in these parameters made for CMR are industrially advantageous. The process by CMR is more economical and ecofriendly than PFR as far as milder process parameters (higher LHSV, lower reactant feed mole ratio, less catalyst require, etc.) and process intensification (reaction and separation in single reactor) are concerned. The study provides new insights for benzene isopropylation reaction. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Benzene; Catalytic membrane reactor; cumene; Diisopropyl benzene; Friedel-Craft alkylation

Variation in acid moiety of polybenzimidazoles: investigation of physico-chemical properties towards their applicability as proton exchange and gas separation membrane materials - Kumbharkar, S. C.; Islam, Md. Nazrul; Potrekar, R. A.; Kharul, Ulhas K. (Polymer, 2009)
A series of polybenzimidazoles (PBIs) were prepared from 3,3'-diaminobenzidine (DAB) and substituted aromatic dicarboxylic acids. Effects of added polarity, bulk and isomerism in the dicarboxylic acid moiety on the properties of formed aromatic polybenzimidazoles were investigated. Solution polycondensation procedure was optimized for individual case of PBI synthesis in order to obtain inherent viscosity of >= 1 dL/g. Analysis of physical properties, water uptake, acid doping (H(3)PO(4) and H(2)SO(4)) and gas permeability was performed. All these PBIs exhibited high thermal stability, good solvent solubility and amorphous nature. The uptake of H(3)PO(4) varied from 9 to 20.1 moles per repeat unit (mol/RU), H(2)SO(4) uptake varied from 3.39 to 3.81 mol/RU, while water uptake varied from 1.8 to 3.6 mol/RU of PBI. The dibromoterephthalic acid and tert-butylisophthalic acid based PBI showed the highest H(3)PO(4) uptake in the series, while tert-butylisophthalic acid based PBI exhibited the highest water uptake. Acid uptake was correlated with swelling of the PBI matrix, while density estimation of H(3)PO(4)-doped PBI by He gas expansion method could be correlated to the physical state of PBI. 5-tert-Butylisophthalic acid and 4,4'-(hexafluoroisopropylidene)bis(benzoic acid) based PBI exhibited higher H(2) and O(2) permeability than other PBIs. The ideal gas selectivity for O(2)/H(2) was considerably higher for most of the PBIs than conventional gas separation membrane materials. These analyses suggested that some of these PBIs have a potential to be used as a PEM or gas separation membrane material. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Gas permeability; Polybenzimidazole; Proton exchange membrane

Artificially designed membranes using phosphonated multiwall carbon nanotube-polybenzimidazole composites for polymer electrolyte fuel cells - Kannan, Ramaiyan; Aher, Pradnya P.; Palaniselvam, Thangavelu; Kurungot, Sreekumar; Kharul, Ulhas K.; Pillai, Vijayamohanan K. (Journal of Physical Chemistry Letters, 2010)
The ability of phosphonated carbon nanotubes to offer an unprecedented approach to tune both proton-conductivity and mechanical stability of hybrid polymer electrolytes based on the polybenzimidazole membrane is demonstrated for fuel cell applications. The covalent attachment between the amino group of the 2-aminoethylphosphonic acid precursor and CNTs has been confirmed by NMR and IR experiments, while EDAX analysis indicates that one out of every 20 carbon atoms is in the CNT is functionalized. Proton conductivity of the composite membrane shows a remarkable 50% improvement in performance while a maximum power density of 780 and 600 mW cm(-2) is obtained for the composite and pristine membranes, respectively. Finally, the ultimate strength determined for the composite and pristine membranes is 100 and 65 MPa, respectively, demonstrating the superiority of the composite. This study opens up a new strategy to systematically tune the properties of polymer electrolytes for special applications by using appropriately functionalized CNTS.

Investigation of gas permeation properties of systematically modified polybenzimidazoles by N-substitution - Kumbharkar, Santosh C.; Kharul, Ulhas K. (Journal of Membrane Science, 2010)
Gas permeation behavior of a series of thermally stable N-substituted polybenzimidazoles by systematically varying bulk and flexibility of the substituent was investigated. Two different PBIs having variation in their acid moiety, viz., PBI-I (based on isophthalic acid) and PBI-BuI (based on 5-tert-butyl isophthalic acid) were selected for N-substitution by alkyl groups possessing different bulk and flexibility. These substituent groups were methyl, n-butyl, methylene trimethylsilane and 4-tert-butylbenzyl. Pure gas sorption and permeability using H(2), N(2), O(2), CH(4) and CO(2) were investigated and correlated with physical properties of formed polymers. Estimation of dual-mode sorption parameters, coefficients of sorption, permeability and diffusion for different gases provided an insight towards effects of nature of a substituent group and parent PBI on governing gas sorption and permeation properties. By changing the substituent group, diffusivity coefficients was found to vary to a larger extent than the solubility coefficient. This significantly enhanced gas permeability for different gases by 1.2-129 times than that of parent PBIs. The permselectivity P(O2)/P(N2) was increased (up to 237%), while for other gas pairs, it was decreased to a different extent. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Diffusion; Gas permeation; N-Substitution; Polybenzimidazole; Sorption

New N-substituted ABPBI: synthesis and evaluation of gas permeation properties - Kumbharkar, Santosh C.; Kharul, Ulhas K. (Journal of Membrane Science, 2010)
Aromatic poly(2,5-benzimidazole), ABPBI was post-modified for the first time to produce organosoluble N-substituted ABPBI. This modification was carried out by N-substitution of ABPBI with bulky alkyl groups, viz., 4-tert-butylbenzyl and methylene trimethylsilyl in an attempt to utilize high rigidity of ABPBI towards gas permeation. These substituted polymers exhibited solubility in common organic solvents, enhancing their processability than ABPBI, which is soluble only in acidic solvents. Considerable decrease in chain packing density led to increase in gas sorption as that of unsubstituted ABPBI. The permeability of pure gases of commercial significance (He, H(2), N(2), O(2), CH(4) and CO(2)) were high, coupled with attractive selectivities. In comparison to conventional PBI, methylene trimethylsilyl substituted ABPBI led to considerably high (33 folds) CO(2) permeability with almost similar selectivity (P(CO2)/P(N2) approximate to 33). Feasibility of these N-substituted ABPBIs to be converted in to required membrane form along with its considerably higher permeation properties depicted the potential of this polymer to be used as gas separation material. Gas diffusion coefficients were estimated from solubility and permeability coefficient. These, along with dual-mode sorption parameters estimated from sorption isotherms provided an insight towards variations in permeation behavior caused by the substitution. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: 5-benzimidazole); Diffusion; Gas permeation; N-Substitution; Poly(2; Sorption

Polyarylate based thin film composite (TFC) membranes: effects of coating parameters, gutter layer, and intrinsic material properties - Chendake, Yogesh J.; Bhole, Yogesh S.; Lohokare, Harshada R.; Kharul, Ulhas K. (Separation Science and Technology, 2010)
Investigations in thin film composite (TFC) membrane formation with polyacrylonitrile ultrafiltration membrane as a support and three polyarylates with sequentially increased polarity are reported. Effects of TFC membrane preparation parameters viz., concentration of the coating solution, dip time, presence of solvent in pores of UF membrane support, and presence of the gutter layer were examined towards the formation of the selective skin layer, which was assessed by gas permeation analysis. TFC membranes prepared using dimethyl bisphenol-A based polyarylate exhibited similar to 3 orders of magnitude higher permeability and comparable selectivity as that of its dense membrane.
Keywords: Gas permeation; gutter layer; polarity; polyarylates; TFC membrane

Pt-MoOx-carbon nanotube redox couple based electrocatalyst as a potential partner with polybenzimidazole membrane for high temperature polymer electrolyte membrane fuel cell applications - Vellacheri, Ranjith; Unni, SreeKuttan M.; Nahire, Sandip; Kharul, Ulhas K.; Kurungot, Sreekumar (Electrochimica Acta, 2010)
A redox couple based electrocatalyst comprising of Pt-Multi Wall Carbon NanoTube (Pt-MWCNT) promoted with molybdenum oxide (MoOx, 2 < x < 3) nanoparticles was prepared. The objective was to effectively organize the Pt-MoOx interface on the smooth MWCNT surface to overcome the practical difficulties associated with establishing such interface with Pt dispersed on carbon morphologies possessing surface irregularities. The present study revealed the importance of stringent controlling of the additive level for maintaining a balanced bifunctional behavior of the catalyst combination through the synergistic effects by the components and the need of a proton conducting membrane operable at high temperature to get better output from the Polymer Electrolyte Membrane Fuel Cell (PEMFC) systems. An indigenously developed polybenzimidazole (PBI) membrane was used to fabricate a membrane electrode assembly (MEA) as it can be operated at higher temperatures compared to that of Nafion membranes. MoOx additive level was carefully controlled by monitoring the active Pt area by cyclic voltammetry. All prepared electrocatalysts were characterized by using HRTEM, XRD and XPS to get information on dispersion and morphology, crystalinity and oxidation state of different elements, respectively. The system prepared with 5% MoOx addition with respect to Pt (hereafter Pt-MoOx(5%)-MWCNT) displayed balanced active Pt area and excellent oxygen reduction reaction (ORR) and methanol oxidation reaction (MOR) activities. Rotating Disk Electrode (ROE) system was extensively utilized to understand the ORR kinetics and the favorable role of MoOx as the promoter in the reaction. The kinetic current (j(k)) measured at 0.02 V vs. Hg/Hg2SO4 electrode from the Koutecky-Levich plots was 9 times higher and the apparent activation energy during single cell evaluation was 27 kJ/mol lower for the MoOx promoted system, compared to the system without the additive. A higher operating temperature significantly favored the cell performance by a combined effect of enhancement in proton conductivity of the PBI membrane and possible kinetic benefit by the well postulated oxygen spill over effect by the MoOx type systems in some combinations involving such systems. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Methanol oxidation reaction; MWCNT; oxygen reduction reaction; PBI membrane; PEMFC

Improved performance of phosphonated carbon nanotube-polybenzimidazole composite membranes in proton exchange membrane fuel cells - Kannan, Ramaiyan; Kagalwala, Husain N.; Chaudhari, Harshal D.; Kharul, Ulhas K.; Kurungot, Sreekumar; Pillai, Vijayamohanan K. (Journal of Materials Chemistry, 2011)
Development of thermally stable polymer electrolyte membranes with higher proton conductivity as well as mechanical stability is a key challenge in commercializing PEM fuel cells operating above 100 degrees C. Polybenzimidazole membranes are one of the promising candidates in this category although with limited mechanical stability and moderate proton conductivity. Here the incorporation of functionalized MWCNT is shown to increase both these key parameters of the polybenzimidazole membranes. Further, formation of a domain like structure after the incorporation of phosphonated MWCNTs (P-MWCNTs) in phosphoric acid doped polybenzimidazole membranes is demonstrated. The enhanced performance has been attributed to the formation of proton conducting networks that formed along the sidewalls of P-MWCNTs with a domain size of 17 nm as estimated from the small angle X-ray scattering measurements. Membrane electrode assembly (MEA) impedance measurements further reveal that the activation energy of oxygen reduction reaction (ORR) reduced for the composite membranes with enhanced proton conductivity. In addition, the mechanical strength measurements reveal a significant improvement in the yield strength and ultimate strength. Also, the mechanical strength of the composite membrane has been increased significantly as indicated by the improvement in the ultimate strength from 65 MPa to 100 MPa for the pristine and composite membranes, respectively. The optimum loading of P-MWCNTs is found to be 1% as inferred from the polarization measurements carried out using pure hydrogen and oxygen. Thus, this study provides a unique opportunity to tune the properties of polymer electrolytes to prepare application oriented hybrid membranes using CNTs with tailor-made functional groups.

Poly(acrylonitrile) based ultrafiltration membranes: optimization of preparation parameters - Lohokare, Harshada R.; Bhole, Yogesh S.; Taralkar, Suyog; Kharul, Ulhas K. (Desalination, 2011)
Supported ultrafiltration (UF) membranes based on poly(acrylonitrile) were prepared while varying crucial parameters responsible for controlling membrane porosity, viz.; polymer concentration, solvent and additives in the dope solution. Insight into membrane porosity and morphology was obtained by water flux, solute rejection, bubble point, pore size distribution, SEM and AFM analyses. It was found that merely increasing polymer concentration does not necessarily reduce pore size of membranes. Among four solvents used for the dope solution preparation, N-methyl pyrrolidone was found to offer membranes with optimal combination of flux and rejection of various solutes. Some of the PAN(17) (17% w/w PAN concentration in the dope solution) membranes prepared using organic acid as the additive (citric acid, tartaric acid or maleic acid) offered 1.2-1.7 times higher flux than the membrane prepared using inorganic salt, ZnCl2 as an additive. The porosity of PAN(17) membrane prepared using CA as an additive was larger as compared to membrane prepared using ZnCl2 as an additive. Atomic force microscopy (AFM) analysis of this membrane exhibited higher surface roughness as compared to the ZnCl2 based membrane. Both these membranes exhibited bacteria (E. Coli) log reduction value (LRV) of at least 6; depicting applicability of these membrane for water disinfection. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Additive; Bacteria rejection; Poly(acrylonitrile); Pore size distribution; Ultrafiltration

Polybenzimidazoles based on 3,3 `-diaminobenzidine and aliphatic dicarboxylic acids: synthesis and evaluation of physicochemical properties toward their applicability as proton exchange and gas separation membrane material - Bhavsar, Rupesh S.; Nahire, Sandip B.; Kale, Mrunali S.; Patil, Shubhangi G.; Aher, Pradnya P.; Bhavsar, Ritesh A.; Kharul, Ulhas K. (Journal of Applied Polymer Science, 2011)
A series of aromatic-aliphatic polybenzimidazoles (PBIs) based on 3,3'-diaminobenzidine (DAB) and aliphatic dicarboxylic acid with incremental -CH2- groups were synthesized. Optimization of synthesis parameters and evaluation of physicochemical properties are requisite for PBI applicability as the proton exchange membrane (PEM) and gas separation membrane materials are reported. It was found that though all these PBIs exhibited high thermal, mechanical, and oxidative stability, effect of added flexibility on physical properties is not monotonous. Membranes were prepared by solution casting as well as phase-inversion method. The later types of membranes exhibited much higher H3PO4 content than its doping achieved in the solution casted membranes. These PBIs possess low hydrogen and helium permeability than that of conventional PBI. This low permeability, along with their excellent oxidative stability indicated that they can be promising PEM materials. Their CO2-sorption analysis revealed that PBI6 based on suberic acid possesses appreciable CO2 sorption. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 120: 1090-1099, 2011
Keywords: Gas permeation; mechanical properties; membranes; oxidative stability; polybenzimidazoles

Polybenzimidazole mediated N-doping along the inner and outer surfaces of a carbon nanofiber and its oxygen reduction properties - Balan, Beena K.; Manissery, Aiswarya Padinhare; Chaudhari, Harshal D.; Kharul, Ulhas K.; Kurungot, Sreekumar (Journal of Materials Chemistry, 2012)
Nitrogen-doped (N-doped) hollow carbon nanofiber (CNF) was synthesized by incorporating a nitrogen containing polymer precursor, polybenzimidazole (PBI-BuI), in the inner cavity as well as on the outer walls of the CNF, followed by a high temperature treatment. PBI-BuI incorporation along the inner and outer surface of the CNF was accomplished by synthesizing a low molecular weight polymer by tuning the synthetic parameters. The solution concentration of the PBI-BuI is also varied to facilitate its entry into the CNF by capillary action. The high temperature treatment (700-1000 degrees C) of the resulting CNF-PBI material decomposes the polymer and induces N-doping along the inner and outer surfaces of the CNF. The initial PBI-BuI content and the annealing temperature are also systematically varied to choose the right combination of starting precursors and heat-treatment conditions. Detailed X-ray photoelectron spectroscopy analysis of the samples shows that pyridinic-type nitrogen is the major component in all the samples. Electrochemical characterizations of this material using cyclic voltammetry, rotating disc electrode studies and durability analysis demonstrated that this material can act as a metal-free oxygen reduction electrocatalyst with improved oxygen reduction kinetics and stability. It is also revealed that the onset potential, limiting current density, number of transferred electrons, etc. have a strong dependence on the annealing temperature.

Polymeric ionic liquids (PILs): effect of anion variation on their CO2 sorption - Bhavsar, Rupesh S.; Kumbharkar, Santosh C.; Kharul, Ulhas K. (Journal of Membrane Science, 2012)
A series of polymeric ionic liquids (PILs) based on poly(diallyldimethylammonium chloride), P[DADMA][Cl] as a precursor was investigated by varying anions categorized into carboxylates, sulphonates and inorganic type. For the exchange of chloride from P[DADMA][Cl] by another anion, silver salt of the corresponding anion was preferred. Obtained PILs were investigated for physical properties which are anticipated to affect gas sorption. PILs possessing carboxylate (especially acetate) anion exhibited attractive CO2 sorption capacity as well as sorption selectivity over H-2 and N-2, in Comparison to Other two Categories. PIL with acetate anion, P[DADMA][Ac] possessed appreciable CO2 sorption coupled with high selectivity (S-CO2/S-N2 = 114.3). This crucial finding from this series of PILs was further substantiated by making PIL based on poly(vinylbenzyltrimethylammonium chloride), P[VBTMA][Cl] as a precursor. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Anion exchange; CO2 sorption; Polymeric ionic liquid

Transport of inorganic acids through polybenzimidazole (PBI) based membranes by chemo-dialysis - Chendake, Yogesh J.; Kharul, Ulhas K. (Desalination and Water Treatment, 2012)
A process of chemo-dialysis involving poly(benzimidazole) (PBI) as a chemically active membrane material is proposed for the transport of inorganic acids. These membranes possessing basic nature selectively bind acid molecules present in the feed solution due to acid-base interactions. They are transported across the membrane by concentration gradient as the driving force. The transported acid molecules are stripped away from other side of the membrane surface by a suitable stripping agent or water. Effects of nature of feed acid (pK(a), molecular size), its concentration in the feed solution and the nature of stripping agent (base or water) on acid transport properties are presented. Membranes showed appreciable transport rates for three acids, viz., H2SO4, HCl and HNO3. The fluxes for different acids varied from 16.1 to 140.7 g/m(2) h under different operating conditions. Most significantly, there was no transport of non-acidic solutes such as NaCl or glucose. This could be made possible since these solutes neither get sorbed in the membrane matrix, nor does the membrane exhibit any porosity for the transport to occur through pores. This resulted in practically infinite selectivity of transported acid over the non-acidic solutes. Use of water as the stripping agent allows recycling of the acid, making the process economically attractive. Moreover, possible recovery of acid and its reuse eliminated the requirement of acid neutralization and disposal; which is a routine practice followed today. Thus, this process of chemo-dialysis is economically attractive and environmentally benign.
Keywords: Acid transport; Chemical interaction; Chemo-dialysis; Inorganic acids; Membrane; Polybenzimidazole

Carbon nanofiber-RuO2-poly(benzimidazole) ternary hybrids for improved supercapacitor performance - Balan, Beena K.; Chaudhari, Harshal D.; Kharul, Ulhas K.; Kurungot, Sreekumar (RSC Advances, 2013)
Carbon nanofiber-RuO2-poly(benzimidazole) ternary hybrid electrode material which integrates dual wall decoration and interfacial area tuning for supercapacitor applications has been devised based on a simple approach. This is achieved by decorating RuO2 nanoparticles of size ca. 2-3 nm along the inner and outer walls of a hollow carbon nanofiber (CNF) support (F-20RuO(2)). In the next step, a proton conducting polymer, phosphoric acid doped polybenzimidazole (PBI-BuI), interface is created along the inner and outer surfaces of this material. A 103% increase in the specific capacitance is obtained for RuO2-PBI hybrid material as compared to that of F-20RuO(2) at the optimum level of the polymer wrapping. Apart from the high specific capacitance, the RuO2-PBI hybrid materials exhibit enhanced rate capability and excellent electrochemical stability of 98% retention in the capacitance. Such a remarkably high activity can be primarily attributed to the efficient dispersion of active sites achieved by properly utilizing inner and outer surfaces of CNF. Apart from this, the facile routes for ion transport created as a result of PBI incorporation coupled with excellent interfacial contact between the RuO2 and the electrolyte resulting in the improved utilization of the active material also contribute to the improved activity. In addition to this, the synergistic effects of pseudocapacitive contribution from both the PBI-BuI and RuO2 also contribute to the redefined performance characteristics.

Effect of foulants on arsenic rejection via polyacrylonitrile ultrafiltration (UF) membrane - Agarwal, Gopal P.; Karan, Raj; Bharti, Sachin; Kumar, Hemant; Jhunjhunwala, Sumit; Sreekrishnan, T. R.; Kharul, Ulhas K. (Desalination, 2013)
Arsenic rejection via modified polyacrylonitrile ultrafiltration (UF) membrane was found to be very high, however, the presence of commonly found foulants in arsenic solution affected membrane performance. The effect of commonly found foulants, such as ovalbumin, humic acid and egg white on arsenic rejection were studied. Experiments indicated that the As(V) rejection was affected by the total quantity of proteins and not the variety of proteins present in a solution. As(V) rejection was found to decrease with increasing proteins while fouling was found to increase from 25% for 0.1 mg/ml to 33% for 0.5 mg/ml egg white. The As(V) rejection was found to decrease with increasing concentration of humic acid for PAN membranes. Fouling studies showed that humic acid was a lesser foulant in comparison to egg white. However a combination of the two foulants led to a decrease in the overall fouling. pH was also found to be a very important factor for egg white dissolution and As(V) rejection. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Arsenic rejection; Egg white; Humic acid; Ovalbumin; Polyacrylonitrile; Ultrafiltration

Effect of the viscosity of poly(benzimidazole) on the performance of a multifunctional electrocatalyst with an ideal interfacial structure - Balan, Beena K.; Unni, Bipinlal; Chaudhari, Harshal D.; Kharul, Ulhas K.; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2013)
A novel electrocatalyst system with unique multifunctional characteristics, originated by the presence of a proton conducting polybenzimidazole (PBI-BuI) bound layer and electron conducting hollow carbon nanofibers (CNF) with catalytically active Pt nanoparticles, has been devised based on a simple strategy. This was achieved by decorating Pt nanoparticles along the inner cavity, as well as on the outer walls of the hollow CNF support (F-Pt). In a further extension, a low molecular weight PBI, synthesized by optimizing the experimental parameters, was incorporated into the inner cavity and along the outer surfaces of F-Pt. Excellent dispersion of the Pt nanoparticles was achieved by properly utilizing the available carbon surface results in improved electrocatalytic activity, while the CNF backbone ensures high electron conductivity as well. The polymer binder coverage formed along the inner and outer wall surfaces provides an efficient triple phase boundary (TPB) around the Pt nanoparticles to facilitate the electrode reactions. The amount and the viscosity of the PBI-BuI in the electrode material were systematically varied to study the influence on the electrochemical performance. Transmission electron microscopy analysis confirms PBI insertion into the tubular cavity of CNF. Pore size distribution analysis implies that both the viscosity and the amount of PBI-BuI have a pivotal role in defining the microstructure of the electrode. Electrochemical studies using cyclic voltammetry (CV) and rotating disc electrode (RDE) reveal the exceptionally high activity of this hybrid material with an improved electrochemically active area. The significant improvement for the oxygen reduction reaction is further confirmed by the single cell analysis also. The high power density displayed by the PBI-BuI based system, as compared to the Nafion based system, validates the conceptualization of the well controlled triple-phase boundary in the system. These results demonstrate that PBI-BuI has a constructive effect in tuning the electrochemical activity at an optimum amount and at a favourable viscosity of the proton conducting polymer.

In situ growth of metal-organic frameworks on a porous ultrafiltration membrane for gas separation - Nagaraju, Divya; Bhagat, Deepti G.; Banerjee, Rahul; Kharul, Ulhas K. (Journal of Materials Chemistry A, 2013)
We demonstrate the synthesis of CuBTC and ZIF-8 on a polysulfone based porous asymmetric ultrafiltration (UF) membrane by in situ growth followed by the LBL deposition of crystals without any need for preseeding or surface modification of the membrane. In this way, the top surface of the UF membrane pores is completely covered by MOFs; while the remaining part of the membrane offers a flexible support to the MOFs. The pore apertures of the MOF nanoparticles located at the pore opening of the UF membrane act as channels for the entry of penetrants. The remaining porous sublayer of the membrane carries penetrants on the permeate side without significant resistance. These composite membranes were characterized by PXRD and SEM. The gas permeation study was performed using pure gases of industrial significance (H-2, C3H6 and CO2). The performance of CuBTC@PSF showed enhanced selectivity, of 7.2 and 5.7 for H-2/CO2 and H-2/C3H6 respectively, to that of the pristine PSF membrane.

Film forming polymeric ionic liquids (PILs) based on polybenzimidazoles for CO2 separation - Kumbharkar, Santosh C.; Bhavsar, Rupesh S.; Kharul, Ulhas K. (RSC Advances, 2014)
PILs are emerging as promising materials for CO2 capture. Film formation, which is a requisite for membrane formation, is induced in a family of PILs by N-substituting a rigid thermo-mechanically stable polybenzimidazole, followed by metathesis. This provided two IL groups per repeat unit of the PIL and enhanced the CO2 separation characteristics.

Fluorescent polymeric ionic liquids for the detection of nitroaromatic explosives - Shaligram, Sayali; Wadgaonkar, Prakash P.; Kharul, Ulhas K. (Journal of Materials Chemistry A, 2014)
We report, for the first time, applicability of film forming polymeric ionic liquids (PILs) possessing pyrene and anthracene fluorophores for the detection of nitroaromatics (NACs). These functionalized PILs were synthesized via post modification of thermo-chemically and mechanically stable polybenzimidazole (PBI). Formed PILs were evaluated for their ability to detect NACs through quenching of fluorescence intensity. Quenching of fluorescence intensity in solution state for NACs, such as nitrobenzene (NB), 2,4,6-trinitrotoluene (TNT) and picric acid (PA), was found to be rapid in both the PILs possessing pyrene and anthracene. The solution-phase Stern-Volmer quenching constants for PA were higher than for other NACs. After these promising results, self-standing films (similar to 12 mm thick) were also evaluated for fluorescence quenching by NACs as well as possible interferents of different nature. These films also exhibited rapid and selective fluorescence quenching when exposed to the saturated vapors of NACs at ambient temperature and pressure. Fluorescence emission of PIL films was affected little by the presence of commonly found interferents. Furthermore, fluorescence intensity could be recovered after the quenching, enabling the reuse of these PIL films for detection of NACs. Smart performance of these films and ease of preparation qualify them as attractive candidates in developing sensor devices for sensitive NACs detection in presence of possible interferents.

Investigation of gas permeation properties of film forming polymeric ionic liquids (PILs) based on polybenzimidazoles - Bhavsar, Rupesh S.; Kumbharkar, Santosh C.; Kharul, Ulhas K. (Journal of Membrane Science, 2014)
Polymeric ionic liquids (PILs) are emerging as new generation membrane materials for CO2 separation. Gas permeation properties of a recently developed PIL family based on three structurally different polybenzimidazoles (PBIs) possessing excellent film forming characteristics are reported. Effects of cationic backbone and anions on gas permeation properties of PILs using pure gases (He, H-2, N-2, CH4, and CO2) were examined at 20 atm upstream pressure and correlated with their physical properties. In comparison to the parent PBIs, PILs exhibited generally higher CO2 permeability, without largely affecting CO2 based selectivity. Some of these PILs exhibiting high PCO2/PCH4, selectivity and P-H2/P-CO2, approaching similar to 1 indicated dominance of CO2 sorption over diffusion. The CO2 sorption specificity of these PILs was distinctly observed based on their improved S-CO2/S-N2, S-CO2/S-CH4 and S-CO2/S-H2 selectivity than their parent PBIs. A large variation in permeation properties of PILs based on a common polycation but different anions indicated that anions play a crucial role on governing gas permeation properties of these PILs. (C) 2014 Elsevier B.V. All rights reserved
Keywords: Gas permeation; Membranes for CO2 separation; Polybenzimidazole; Polymeric ionic liquid

New approach of blending polymeric ionic liquid with polybenzimidazole (PBI) for enhancing physical and electrochemical properties - Rewar, Anita S.; Chaudhari, Harshal D.; Illathvalappil, Rajith; Sreekumar, K.; Kharul, Ulhas K. (Journal of Materials Chemistry A, 2014)
Although the use of ionic liquids (IL) in polymeric membranes is known to elevate the electrochemical performance for proton exchange membrane-based fuel cells (PEMFC), they suffer from drawbacks such as IL drain and lowering in mechanical properties that lead to deterioration in PEMFC performance. To mitigate these issues, we report, for the first time, the use of polymeric ionic liquid (PIL), namely, poly(diallyl dimethyl ammonium trifluoride methane sulphonate) (P[DADMA][TFMS]) to be blended with polybenzimidazole (PBI-I) as a membrane material for PEMFC. PBI-I and (P[DADMA][TFMS]) were chosen because they form miscible blends and are suitable for acid doping as a matrix, which can eventually be used as proton conductor. The structure, miscibility and inter-polymer interactions were studied by infrared (IR) spectroscopy and differential scanning calorimetry (DSC). The increase in proton conduction in comparison to the PBI membranes was observed due to the presence of ionic groups of PILs in blend membranes. With the increase in PIL content, the proton conductivity of the composite membranes gradually increased from 0.04 S cm(-1) for PBI to 0.07 S cm(-1) for the blend membrane at 150 degrees C. The MEAs were fabricated with PBI-I, PBI-PIL15, PBI-PIL25 and PBI-PIL35. Corresponding single cells were successfully tested at temperatures of 160 degrees C. The maximum power density and current density obtained were 515 mW cm(-2) and 1632 mA cm(-2), respectively, for PBI-PIL25-based MEA.

PBI-BuI and PAN-PSSALi based UF membranes: effects of solute and membrane surface interactions on rejection and flux - Bhagat, Deepti G.; Mule, Bhavana; Mandlekar, Neeraj; Pandare, Kiran; Kharul, Ulhas K. (Desalination, 2014)
Ultrafiltration membrane using tert-butylpolybenzimidazole (PBI-BuI) was prepared and characterized for flux and rejection performance using Gel Permeation Chromatography (GPC). Polyethylene glycol (PEG) and polyethylene oxide (PEO) with different molecular weights were used as the solutes. While using feed solution containing mixture of PEGs, higher rejection was observed than using individual PEG. The water flux of PBI-BuI membrane after passing individual PEG solutions showed considerable (similar to 36%) reduction, which could be attributable to the PEG adsorption on the membrane pore surface. PEG adsorption was further substantiated by SEM, IR and TGA. The amphoteric nature of PBI-BuI could cause H-bonding between membrane surface and PEG molecules, leading to PEG adsorption on the membrane and pore surface. To ascertain this postulation, a study with PAN-PSSALi (which does not contain H-bonding) based UF membrane containing negatively charged -SO3- group was done. It was found that PEG adsorption in this case is not as predominant as in earlier case. This membrane showed marginal reduction in water flux of 8%, vis-a-vis 36% reduction shown by PBI-BuI based membrane. This indicated that H-bonding present in PBI-BuI is mainly responsible for the PEG adsorption on its membrane and pore surface, in spite of PEG being a neutral molecule. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Gel permeation chromatography; Polybenzimidazole; Rejection; Solute adsorption; Ultrafiltration

Polybenzimidazole based film forming polymeric ionic liquids: synthesis and effects of cation-anion variation on their physical properties - Bhavsar, Rupesh S.; Kumbharkar, Santosh C.; Rewar, Anita S.; Kharul, Ulhas K. (Polymer Chemistry, 2014)
Polymeric ionic liquids (PILs) are gaining wide attention due to their tunable properties and applicability in various upcoming areas, including membranes for CO2 separation. The known methodologies yield PILs that are difficult to convert into film form. The present work investigates a synthetic approach for obtaining PILs based on a strong film forming with a fully aromatic rigid backbone while incorporating ionic liquid character in it. Three structurally different polybenzimidazoles (PBI-I, PBI-BuI and ABPBI) were N-quaternized by a methyl group, followed by iodide exchange with various promising anions. The extent of iodide exchange by another anion was high enough (>94% in most cases). Most of the resulting PILs with various anions offer mechanically strong films, with the exception of those based on acetate and benzoate as an anion. Although the base PBI has excellent film forming ability, this result conveyed the role of anion in governing the film forming ability of the PIL. Salient features of this methodology include a fully aromatic polycation backbone, wide structural tunability (by virtue of variation not only of the anion/cation, but also with N-substituent) and introducing two IL characters per repeat unit of a PIL (except for PILs based on ABPBI). Attempted PIL structural variations showed diverse property variations in bulk and surface properties (solvent solubility, contact angle, water sorption, thermal stability, polyelectrolyte behaviour, CO2 sorption and ionic conductivity). Mechanical properties of film forming PILs exhibited high enough tensile strength, conveying their applicability as membrane materials.

ZIF-8@PBI-Bul composite membranes: elegant effects of PBI structural variations on gas permeation performance - Bhaskar, Anand; Banerjee, Rahul; Kharul, Ulhas K. (Journal of Materials Chemistry A, 2014)
The composites of metal organic frameworks (MOFs) and polymers look promising as membrane materials for gas separation, provided benefits of both the components can be shown successfully. This work shows that the structural architecture of polybenzimidazole (PBI) is highly advantageous in offering attractive gas permeation properties of its composites with MOFs. PBI-Bul and its N-substituted (methyl and 4-tert-butylbenzyl) derivatives were blended with ZIF-8. In general, homogeneous blend formation of ZIF-8 was achieved with all three polymers, as supported by SEM. Wide angle X-ray diffraction, mechanical property analysis and density measurements of the composite membranes were performed in order to understand the effects of physical blending of MOFs and polymers. Gas permeability analysis of the composite membranes revealed that the properties of MOFs as well as those of polymers arising from their structural architecture are responsible for governing the permeability and selectivity of the resulting composites.

Polybenzimidazole based polymeric ionic liquids (PILs): effects of controlled degree of N-quaternization on physical and gas permeation properties - Rewar, Anita S.; Bhavsar, Rupesh S.; Sreekumar, K.; Kharul, Ulhas K. (Journal of Membrane Science, 2015)
Polymeric ionic liquids (PILs) are gaining increasing attention as potential membrane materials to be employed for CO2 separation. With a goal to improve gas permeability, this work presents a series of film forming PlLs obtained by controlled degree of N-quaternization (DQ) of PBI-BuI using a bulky 4-tertbutylbenzyl group. Concurrent effects of variation in ionic content and bulky group substitution were analyzed for physical and gas permeation properties of the resulting PILs. Attempted structural variations leading to simultaneous increments in ionic content and bulky groups offered amorphous polymers with acceptable thermal stability and non-monotonous chain packing density. Enhancement in pure gas permeability coupled with appreciable selectivity for various gas pairs was in accordance with the packing density variations in the series. Gas permeability showed maxima at DQ of just 13%. This conveyed that effects of bulky group substitution in retarding chain packing are overcome by attractive ionic interactions at much lower DQ in these PILs ionic interactions are thus more predominant in governing chain packing and gas permeation properties. These PILs possessed 3.3-20 times higher CO2 permeability in comparison to their parent PBI-BuI, without a significant loss in selectivity. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Degree of quaternization; Gas permeation; Polybenzimidazole; Polymeric ionic liquid

Polybenzimidazole-based polymeric ionic liquids (PILs): effects of `substitution asymmetry' on CO2 permeation properties - Shaligram, Sayali V.; Wadgaonkar, Prakash P.; Kharul, Ulhas K. (Journal of Membrane Science, 2015)
Polymeric Ionic Liquids (PILs) are being considered as promising membrane materials for CO2 separation. Present work aims at investigating effects substitution asymmetry on imidazole moiety of two structurally different polybenzimidazoles (PBI-BuI and PBI-HFA) on physical, gas sorption and transport properties of the resulting film forming PILs possessing symmetric substitution, while keeping one of the N-substituent as methyl group. PILs were obtained with high degree of substitution. The halide anion of these PILs was exchanged with BF4-, Tf-2(N) over bar and HF (B) over bar anions. Effects of substituents, cationic backbone and type of anions on gas permeation properties of PILs using pure gases (He, H-2, N-2 and CO2) were examined at 20 atm upstream pressure and correlated with their physical properties. Combination of typical ionic liquid character (effective towards enhancing CO2 sorption) and looser chain packing (ease in gas diffusion) offered improved CO2 permeation characteristics. As an outcome, some of the PILs exhibited higher CO2 permeation than that of hydrogen, typically known as `reverse selectivity'. These asymmetrically substituted PILs enhanced not only the gas permeability, but also selectivity than their symmetrically substituted counterparts. (C) 2015 Elsevier B.V. All rights reserved.

Pore surface engineering in porous, chemically stable covalent organic frameworks for water adsorption - Biswal, Bishnu P.; Kandambeth, Sharath; Chandra, Suman; Shinde, Digambar Balaji; Bera, Saibal; Karak, Suvendu; Garai, Bikash; Kharul, Ulhas K.; Banerjee, Rahul (Journal of Materials Chemistry A, 2015)
Herein, we have explored the possibility of a class of covalent organic frameworks (COFs) as water adsorbing materials. We have selected, synthesized 12 chemically stable functionalized Schiff base COFs and thoroughly studied their water uptake behaviour. Further, a deep understanding was developed with these COFs towards the effects of condensation pressure of water and hydrophilic/hydrophobic groups present in the COF pores on water absorption capacity and ultimately, their recyclability. Among all reported COFs, TpPa-1 shows the highest water uptake of 30 wt% (368 cm(3) g(-1); 17 mmol g(-1)) at P/P-0 = 0.3, which is also comparable with the recently reported carbon materials and few well known MOFs. This study also reveals that the overall water uptake of COFs can be tuned systematically based on chemical functionality and pore size in a wider window of relative pressures.

Selective interfacial synthesis of metal-organic frameworks on a polybenzimidazole hollow fiber membrane for gas separation - Biswal, Bishnu P.; Bhaskar, Anand; Banerjee, Rahul; Kharul, Ulhas K. (Nanoscale, 2015)
Metal-organic frameworks (MOFs) have gained immense attention as new age materials due to their tuneable properties and diverse applicability. However, efforts on developing promising materials for membrane based gas separation, and control over the crystal growth positions on polymeric hollow fiber membranes still remain key challenges. In this investigation, a new, convenient and scalable room temperature interfacial method for growing MOFs (ZIF-8 and CuBTC) on either the outer or inner side of a polybenzimidazole based hollow fiber (PBI-BuI-HF) membrane surface has been achieved in a controlled manner. This was made possible by the appropriate selection of an immiscible solvent pair and the synthetic conditions. The growth of MOFs on the PBI-BuI-HF membrane by the interfacial method was continuous and showed an appreciable gas separation performance, conveying promise for their applicability.

Characterizing the nanoclay induced constrained amorphous region in model segmented polyurethane-urea/clay nanocomposites and its implications on gas barrier properties - Rath, Sangram K.; Sudarshan, Kathi; Bhavsar, Rupesh S.; Kharul, Ulhas K.; Pujari, Pradeep K.; Patri, Manoranjan; Khakhar, Devang V. (Physical Chemistry Chemical Physics, 2016)
There has been an increasing recognition of the fact that purely geometric factors associated with clay platelet dispersion in a polymer matrix cannot adequately explain the barrier properties of polymer/clay nanocomposites. The objective of the present work is to understand the nanoclay induced structural changes in a polyurethane-urea matrix and clay dispersion at different length scales using segment-specific characterization techniques and implications of the same in gas barrier properties using He, N-2 and CO2 as probe molecules. Wide angle X-ray diffraction (WAXD) and positron annihilation life time spectroscopy (PALS) studies revealed nanoclay induced alterations in the chain packing of the amorphous soft segments of the polyurethane matrix at a molecular scale of a few Angstroms. The hard segment organization and the phase morphology of the nanocomposites, spanning length scales of several nanometers, were investigated by small angle X-ray scattering (SAXS), scanning electron microscopy (SEM) and atomic force microscopy (AFM). Furthermore, the presence of a constrained amorphous region surrounding the nanoclay was confirmed from AFM, WAXD and PALS results. Several pertinent structural variables from the gas transport point of view were deduced from these characterization techniques to understand the effect of the barrier properties in tandem with the clay dispersion morphology.

Chemically stable covalent organic framework (COF)-polybenzimidazole hybrid membranes: enhanced gas separation through pore modulation - Biswal, Bishnu P.; Chaudhari, Harshal D.; Banerjee, Rahul; Kharul, Ulhas K. (Chemistry-A European Journal, 2016)
Highly flexible, TpPa-1@PBI-BuI and TpBD@PBI-BuI hybrid membranes based on chemically stable covalent organic frameworks (COFs) could be obtained with the polymer. The loading obtained was substantially higher (50%) than generally observed with MOFs. These hybrid membranes show an exciting enhancement in permeability (about sevenfold) with appreciable separation factors for CO2/N-2 and CO2/CH4. Further, we found that with COF pore modulation, the gas permeability can be systematically enhanced.
Keywords: covalent organic frameworks; Gas separation; membranes; microporous materials; pore modulation

Incorporation of rigid polyaromatic groups in polybenzimidazole-based polymeric ionic liquids: assertive effects on gas permeation properties - Shaligram, Sayali V.; Rewar, Anita S.; Wadgaonkar, Prakash P.; Kharul, Ulhas K. (Polymer, 2016)
Polymeric ionic liquids (PILs) have emerged as promising membrane materials for CO2 separation. The present work is aimed at investigating the effects of incorporation of rigid polyaromatic hydrocarbons, viz., pyrene and anthracene, in polybenzimidazole-based PILs. The effects of substituent and anion variation on the gas permeation properties of PILs using pure gases were examined at 20 atm upstream pressure. The results were correlated with physical properties of PILs. The pyrene substituted PIL exhibited similar to 10 fold increase in CO2 permeability as compared to its precursor polymer PBI-BuI. The combination of a CO2 specific anion and bulky group substitution offered higher CO2 permeability as well as appreciable permselectivity than their structural analogue that was devoid of IL functionality. The permeation properties of present PILs were superior to those of conventional glassy polymers such as polysulfone, matrimid and polycarbonate which are widely studied for their gas permeation properties. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Gas permeation; membranes; Polymeric ionic liquids

Polybenzimidazole based polymeric ionic liquids possessing partial ionic character: effects of anion exchange on their gas permeation properties - Rewar, Anita S.; Shaligram, Sayali V.; Kharul, Ulhas K. (Journal of Membrane Science, 2016)
Polymeric ionic liquids (PILs) are emerging as promising membrane materials for CO2 separation. Present work is in continuation with our earlier efforts on evaluating gas permeation properties (especially, CO2) of film forming PILs based on polybenzimidazoles and efforts towards improving their permeability by structural tuning. This work specifically aims at evaluating effect of anion variation in chosen PILs possessing partial N-quaternization of imidazole moiety of PBI-Bul. Three anions (viz., Tf2N-, BF4- and Ac-) were chosen for the bromide exchange of two PILs, viz., [TBzPBI-Bul][Br](10) and [TBzPBI-Bul][Br](18), possessing degree of PEI N-quaternization (DQ) as 10 and 18%, respectively. Concurrent effects of variation in anion and DQ were analyzed in terms of physical and gas permeation properties of the resulting PILs. All of them possessed amorphous nature, adequate thermal stability ( >= 250 degrees C) and solvent solubility, which are primary requisites towards their applicability as a membrane material. PILs possessing BF4- anion exhibited improved CO2 permeability coefficient as well as its permselectivity over CH4 and N-2, in comparison to their counterparts with other anions. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Anion exchange; Gas separation; Polybenzimidazole; Polymeric ionic liquids (PILs)

Synthesis and properties of poly(arylene ether)s based on 3-pentadecyl 4,4'-biphenol - Tawade, Bhausaheb V.; Shaligram, Sayali V.; Valsange, Nitin G.; Kharul, Ulhas K.; Wadgaonkar, Prakash P. (Polymer International, 2016)
A new biphenol, 3-pentadecyl 4,4-biphenol, was synthesized starting from 3-pentadecylphenol and was polycondensed with 4,4-difluorobenzophenone, 1,3-bis(4-fluorobenzoyl)benzene and bis(4-fluorophenyl)sulfone to obtain poly(arylene ether)s with biphenylene linkages in the backbone and pendent pentadecyl chains. Inherent viscosities and number-average molecular weights (M-n) of the poly(arylene ether)s were in the range 0.50 - 0.81 dL g(-1) and 2.2 x 10(4) - 8.3 x 10(4), respectively. Detailed NMR spectroscopic studies of the poly(arylene ether)s indicated the presence of constitutional isomerism which existed because of the non-symmetrical structure of 3-pentadecyl 4,4-biphenol. The poly(arylene ether)s readily dissolved in common organic solvents such as dichloromethane, chloroform and tetrahydrofuran and could be cast into tough, transparent and flexible films from their chloroform solutions. The poly(arylene ether)s exhibited T-g values in the range 35-60 degrees C which are lower than that of reference poly(arylene ether)s without pentadecyl chains. The 10% decomposition temperatures (T-10) of the poly(arylene ether)s were in the range 410-455 degrees C indicating their good thermal stability. A gas permeation study of poly(ether sulfone) containing pendent pentadecyl chains revealed a moderate increase in permeability for helium, hydrogen and oxygen. However, there was a large increase in permeability for carbon dioxide which could be attributed to the internal plasticization effect of pendent pentadecyl chains. (c) 2016 Society of Chemical Industry
Keywords: cashew nut shell liquid (CNSL); gas permeation study; pentadecyl; poly(arylene ether)s; thermal stability

Self-exfoliated guanidinium-based ionic covalent organic nanosheets (iCONs) - Mitra, Shouvik; Kandambeth, Sharath; Biswal, Bishnu P.; Khayum, Abdul M.; Choudhury, Chandan Kumar; Mehta, Mihir R.; Kaur, Gagandeep; Banerjee, Subhrashis; Prabhune, Asmita; Verma, Sandeep; Roy, Sudip; Kharul, Ulhas K.; et al. (Journal of the American Chemical Society, 2017)
Covalent organic nanosheets (CONs) have emerged as functional two-dimensional materials for versatile applications. Although pi-pi stacking between layers, hydrolytic instability, possible restacking prevents their exfoliation on to few thin layered CONs from crystalline porous polymers. We anticipated rational designing of a structure by intrinsic ionic linker could be the solution to produce self-exfoliated CONs without external stimuli. In an attempt to address this issue, we have synthesized three self-exfoliated guanidinium halide based ionic covalent organic nanosheets (iCONs) with antimicrobial property. Self-exfoliation phenomenon has been supported by molecular dynamics (MD) simulation as well. Intrinsic ionic guanidinium unit plays the pivotal role for both self-exfoliation and antibacterial property against both Gram-positive and Gram-negative bacteria. Using such iCONs, we have devised a Mixed matrix membrane which could be useful for antimicrobial coatings with plausible medical benefits.

Design, synthesis, and gas permeation properties of polyimides containing pendent imidazolium groups - Shrimant, Bharat; Kharul, Ulhas K.; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2018)
Film-forming polymers containing ionic groups have attracted considerable attention as emerging materials for gas separation applications. The aim of this article was to synthesize new film-forming polyimides containing imidazolium groups (PI-IMs) and establish their structure-performance relationship. In this context, a new aromatic diamine, namely, N-1-(4-aminophenyl)-N-1-(4-(2-phenyl-1H-imidazol-1-yl)phenyl)benzene-1,4-diamine (ImTPADA), was synthesized and polycondensed with three aromatic dianhydrides, namely, 4,4-(hexafluoroisopropylidene)diphthalic anhydride, 4,4-(4,4-isopropylidenediphenoxy) bis(phthalic anhydride), and 4,4-oxydiphthalic anhydride to form the corresponding polyimides containing pendent 2-phenylimidazole groups (PI-IEs). Next, PI-IMs were prepared by N-quaternization of pendent 2-phenylimidazole groups present in PI-6FDA using methyl iodide followed by anion exchange with bis(trifluoromethane)sulfonimide lithium salt (LiTf2N). PI-IEs and PI-IMs exhibited reasonably high molecular weights, amorphous nature, good solubility, and could be cast into self-standing films from their DMAc solutions. Thermogravimetric analysis showed that 10% weight loss temperature of PI-IEs and PI-IMs were in the range 545-475 degrees C and 303-306 degrees C, respectively. Gas permeability analysis of films of PI-IEs and PI-IMs was investigated by variable-volume method and it was observed that incorporation of ionic groups into PI-6FDA resulted in increased permeability while maintaining selectivity. In particular, polymer bearing Tf2N- anion exhibited high CO2 permeability (33.3 Barr) and high selectivity for CO2/CH4 (41.1) and CO2/N-2 (35.4). (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2018, 56, 1721-1729

Intrinsically microporous polyimides containing spirobisindane and phenazine units: synthesis, characterization and gas permeation properties - Shrimant, Bharat; Dangat, Yuvraj; Kharul, Ulhas K.; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A - Polymer Chemistry, 2018)
A new diamine containing spirobisindane and phenazine units, namely, 3,3,3,3-tetramethyl-2,2,3,3-tetrahydro-1,1-spirobi[cyclopenta[b]phen azine]-7,7-diamine (TTSBIDA) was synthesized starting from commercially available 5,5,6,6-tetrahydroxy-3,3,3,3-tetramethyl-1,1-spirobisindane (TTSBI). TTSBI was oxidized to 3,3,3,3-tetramethyl-2,2,3,3-tetrahydro-1,1-spirobi[indene]-5,5,6,6-tet raone (TTSBIQ) which was subsequently condensed with 4-nitro-1,2-phenylenediamine to obtain 3,3,3,3-tetramethyl-7,7-dinitro-2,2,3,3-tetrahydro-1,1-spirobi[cyclope nta[b]phenazine] (TTSBIDN). TTSBIDN was converted into TTSBIDA by reduction of the nitro groups using hydrazine hydrate in the presence of Pd/C as the catalyst. A series of new polyimides of intrinsic microporosity (PIM-PIs) were synthesized by polycondensation of TTSBIDA with commercially available aromatic dianhydrides. PIM-PIs exhibited amorphous nature, high thermal stability (T-10>480 degrees C) and intrinsic microporosity (BET surface area=59-289 m(2)/g). The gas permeation characteristics of films of selected PIM-PIs were evaluated and they exhibited appreciable gas permeability as well as high selectivity. The CO2 and O-2 permeability of PIM-PIs were in the range 185.4-39.2 and 30.6-6.2 Barrer, respectively. Notably, polyimide derived from TTSBIDA and 4,4-(hexafluoroisopropylidene)diphthalic anhydride (PIM-PI-6FDA) exhibited high CO2 and O-2 permeability of 185.4 and 30.6 Barrer with CO2/CH4 and O-2/N-2 selectivity of 43.1 and 5.1, respectively. The data of PIM-PI-6FDA for CO2/CH4 and O-2/N-2 gas pairs were located near Robeson upper bound. (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2018, 56, 766-775
Keywords: Gas permeability; intrinsic microporosity; polyimides; spirobisindane

Preparation and investigations of ABPBI membrane for HT-PEMFC by immersion precipitation method - Chaudhari, Harshal D.; Illathvalappil, Rajith; Kurungot, Sreekumar; Kharul, Ulhas K. (Journal of Membrane Science, 2018)
Poly(2,5-benzimidazole) (ABPBI) membranes were prepared by an easy and benign 'immersion precipitation' method; alleviating drawbacks of conventional solution casting method involving evaporation of the corrosive solvent. The importance of varying inherent viscosity on the properties of resulting membranes was investigated. The porous membranes formed by immersion precipitation method were analyzed for basic properties (water flux, porosity and dimensional analysis). Since the dense structure is required for their applicability for a fuel cell, through-porosity of the formed membranes was successfully eliminated using a unique shrinkage (similar to 50%) property of ABPBI, initially, at 60 degrees C followed by at higher temperature. The correlation of membranes annealing temperature with the mechanical properties, phosphoric acid doping and proton conductivity was established. The present membranes exhibited high doping level (5.1 mol/RU), proton conductivity (0.083 S cm(-1)) and fuel cell performance. For comparison, solution casted membranes were prepared and analyzed. The OCP (0.91 V) and max power density (766mWcm(-2)) are quite promising features of this new type of membranes.

Spiro [fluorene-9,9 '-xanthene]-containing copolymers of intrinsic microporosity: synthesis, characterization and gas permeation properties - Shrimant, Bharat; Kharul, Ulhas K.; Wadgaonkar, Prakash P. (Reactive & Functional Polymers, 2018)
In the present study, a new bis(catechol) containing spiro[fluorene-9,9'-xanthene], namely, 4,4'-(spiro(fluorene9,9'-xanthene]-2',7'-diyl)bis(benzene-1,2-diol) (THSFX) was designed and synthesized. Polycondensation reactions of THSFX and varying compositions of THSFX and 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobisindane (TTSBI) were carried out with 2,3,5,6-tetrafluoroterephthalonitrile (TFTPN) to obtain a homopolymer and copolymers, respectively. The organo-soluble polymers exhibited reasonably high molecular weights (23300-34,100 g/mol) and could be cast into self-standing films from their chloroform solutions. X-Ray diffraction studies indicated that PIMs were amorphous in nature. These polymers exhibited high thermal stability (T-10 = 490-510 degrees C) and possessed intrinsic microporosity with high BET surface area (360-796 m(2)/g). The gas permeation properties of SFX-PIM-25 and SFX-PIM-33 were evaluated and they exhibited high gas permeability (CO2 = 3595-4034 Barrer). The gas permeability data of SFX-PIM-25 and SFX-PIM-33 was located close to 1991 Robson upper bound for CO2/N-2, CO2/CH4 and O-2/N-2 gas pairs

Synthesis, characterization, and gas permeation properties of adamantane-containing polymers of intrinsic microporosity - Shrimant, Bharat; Shaligram, Sayali V.; Kharul, Ulhas K.; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2018)
A new bis(catechol) monomer, namely, 4,4-((1r,3r)-adamantane-2,2-diyl)bis(benzene-1,2diol) (THADM) was synthesized by condensation of 2-adamantanone with veratrole followed by demethylation of the formed (1r,3r)-2,2-bis(3,4 dimethoxyphenyl)adamantane. Polycondensation of THADM and various compositions of THADM and 5,5,6,6-tetrahydroxy-3,3,3,3-tetramethylspirobisindane was performed with 2,3,5,6-tetrafluoroterephthalonitrile (TFTPN) to obtain the homopolymer and copolymers. These polymers demonstrated good solubility in common organic solvents such as dichloromethane, chloroform, and tetrahydrofuran and could be cast into tough films from their chloroform solutions. GPC analysis revealed that number average molecular weights of polymers were in the range 48,100-61,700 gmol(-1), suggesting the formation of reasonably high molecular weight polymers. They possessed intrinsic microporosity with Brunauer-Emmett-Teller (BET) surface area in the range 703-741 m(2)g(-1). Thermogravimetric analysis of polymers indicated that 10% weight loss temperature was in the range 513-518 degrees C demonstrating their excellent thermal stability. THADM-based polymer of intrinsic microporosity (PIM) showed P(CO2)=1080, P(O-2)=232 and appreciable selectivity [(CO2/CH4)=22.6, (CO2/N-2)=26.7, and (O-2/N-2)= 5.7]. The gas permeability measurements revealed that with increase in the content of adamantane units in PIMs, selectivity increased and permeability decreased, following the trade-off relationship. The gas separation properties of PIMs containing adamantane units were located close to 2008 Robeson upper bound for gas pairs such as CO2/CH4, CO2/N-2, H-2/N-2, and O-2/N-2. (c) 2017 Wiley Periodicals, Inc.
Keywords: adamantane; Gas permeation; intrinsic microporosity; membranes; structure-property relations

Transforming covalent organic framework into thin-film composite membranes for hydrocarbon recovery - Biswal, Bishnu P. (Separation Science and Technology, 2018)
We, for the first time, employed chemically stable covalent organic framework (COF) (TpPa-1) as a transport-active phase within the polymer (styrene-butadiene rubber; SBR) matrix to make TpPa-1@SBR thin-film composite (TFC) membranes. Three composite membranes, viz., TpPa-1(30)@SBR, TpPa-1(50)@SBR, and TpPa-1(70)@SBR have been prepared with varying COF content. These membranes were characterized for gas permeance and results were compared with the pristine SBR-based TFC membrane. The fully organic nature of chemically stable COF offered good compatibility with the host polymer matrix (SBR) and resulted into flexible TFC membranes even at 70% of COF loading; compared to the other porous material (MOFs or Inorganic fillers), it is appreciable.
Keywords: Covalent organic framework; hydrocarbon recovery; propylene–propane; styrene-butadiene rubber; thin film composite

ZIF-8@DBzPBI-BuI composite membranes for olefin/paraffin separation - Kunjattu, Shebeeb H.; Ashok, Varsha; Bhaskar, Anand; Pandare, Kiran; Banerjee, Rahul; Kharul, Ulhas K. (Journal of Membrane Science, 2018)
ZIF-8 is a member of Zeolitic Imidazole Framework family having high internal surface area, the high thermo-chemical stability and ease of synthesis gained immense attention for its highly selective sieving ability. Transforming it into a membrane form and practical utility remains a challenge. Any success towards this direction would radically reduce the cost of propylene/propane separation. Present study reports use of substituted polybenzimidazole (DBzPBI-BuI) for fabrication of flexible, thus scalable composite membranes with ZIF-8 (ZIF8@DBzPBI-BuI) possessing host-guest compatibility. The membrane with 30% ZIF-8 loading showed promising propylene-propane separation (ideal selectivity of 32.7), coupled with propylene permeability of 12.13 Barrer. Analysis of sorption shed light on the high contribution of diffusivity on governing permeation properties of the composite membranes. The mixed gas analysis offered highly encouraging results in comparison to known composite membranes of different polymers with ZIF-8. Placement of present data on `upper-bound' showed a rapid enhancement in selectivity by the addition of ZIF-8 in the polymer matrix, which seems to be a result of the elimination of inter-phase defects. It was made possible due to the functionality of host polymer.
Keywords: Gas permeation; Olefin/paraffin separation; Polybenzimidazole (PBI); ZIF-8

Bimetallic nano alloy architecture on a special polymer: Ni or Cu merged with Pd for the promotion of the Mizoroki-Heck reaction and the Suzuki-Miyaura coupling - Patil, Vijay P.; Kashid, Abhijit A.; Solanki, Bhanupratap S.; Kharul, Ulhas K.; Iyer, Suresh (Journal of Chemical Sciences, 2021)
Novel Ni-Pd and Cu-Pd bimetallic nano alloys was designed and heterogenized on the highly robust ABPBI [poly(2,5-benzimidazole)] polymer in high yields using NaBH4 as reducing agent. These were versatile ligand free catalysts for the Mizoroki-Heck reaction and Suzuki-Miyaura coupling. The bimetallic Ni-Pd-ABPBI catalyst for the Mizoroki-Heck reaction of 4-iodo anisole could be recycled 5 times with high yields. Aryl bromides could also be activated for the Mizoroki-Heck reaction using Cu-Pd-ABPBI NP catalysts, with moderate yields. Graphic abstractSynopsis Novel bimetallic Ni-Pd and Cu-Pd nano alloys, heterogenized on the robust ABPBI [poly(2,5-benzimidazole)] polymer using NaBH4 as reducing agent, is described. These were versatile ligand free, noble metal conservative catalysts, for the Mizoroki-Heck reaction and the Suzuki-Miyaura coupling. Aryl bromides were activated for the Mizoroki-Heck reaction using the Cu-Pd-ABPBI catalyst.
Keywords: Bimetallic nano alloys; Cu-Pd-ABPBI; Mizoroki-Heck reaction; Ni-Pd-ABPBI; Suzuki coupling

Tuning the selectivity of CO2 hydrogenation using ceramic hollow fiber catalytic modules - Jogdand, Shunottara M.; Bedadur, Prachiti R.; Torris, Arun; Kharul, Ulhas K.; Naidu, V. Satyam; Devi, R. Nandini (Reaction Chemistry & Engineering, 2021)
The unique structural features and advantageous pore distributions of alumina hollow fibers can be exploited to tune the selectivity in heterogeneous catalysis. Formation of a finger-like cavity structure is the unique characteristic of the phase inversion method, which provides a larger surface area to volume ratio desirable for catalytic reactions. This feature, along with a highly porous sandwiched skin layer, makes this architecture superior to conventional powder catalysts or other structured catalyst forms like monoliths. Alumina hollow fibers are prepared by the modified phase inversion method and characterized for their pore size and distribution. Ni metal nanoparticles are uniformly deposited in the Al2O3 hollow fibers to prepare a Ni/Al2O3 catalyst and tested for the CO2 methanation reaction. Suitable reactor and catalyst loading methods are designed and optimized to achieve higher CO2 to methane conversion in a temperature range of 225 to 400 degrees C. The alpha-alumina phase, which is usually reported to be a poor support for Ni in CO2 methanation in the conventional fixed bed configuration, showed high activity when modulated as hollow fibers. Also, the selectivity to CH4 is enhanced and minimal CO formation is observed. The kinetic rate expressions are simulated for the prediction of methane and CO gas evolution at the outlet with temperature. The experimental results for the gas composition are in good agreement with the model predictions. The advantage of such a module reactor is explained based on the mass transfer limitations and consequently the reaction time constants arrived at from the predicted gas compositions.

Addressing challenges in sealing of scalable multifiber module for O-2 enrichment using LSCF membranes - Jogdand, Shunottara M.; Bedadur, Prachiti R.; Torris, Arun; Agrawal, Ravi; Kharul, Ulhas K.; Devi, R. Nandini (International Journal of Applied Ceramic Technology, 2022)
Scalable and multifiber modules in oxygen separation face huge challenges due to difficulty in integrating all the necessary components, especially in sealing the fibers in a gas tight module. Here, we report our findings on design and fabrication of a multifiber La0.6Sr0.4Co0.2Fe0.8O3-delta (LSCF)-based module, which can be scaled up. The focus is on sealing ceramic-metal interfaces by layering of sealants of varying thermal properties. We have also incorporated the use of dead ended fibers to minimize ceramic-metal interfaces in the hot zones and present a new method for dead ending by flame melting. Pressurizing the air inlet feed from either bore side or shell side is detrimental to the structural integrity of the fibers. A thorough characterization of the fresh and spent fibers is also carried out using X-ray tomography and electron microscopy, which indicates effect of temperature and pressure on the fibers.
Keywords: Characterization; permeability; Perovskites

PPO-ZIF MMMs possessing metal-polymer interactions for propane/ propylene separation - Kunjattu, H. Shebeeb; Kharul, Ulhas K. (Journal of Membrane Science, 2023)
An assertive formation of ZIF-based mixed matrix membranes (MMMs) with polyphenylene oxide (PPO), a high permeability polymer as a host, is presented. The interfacial interactions between the filler particles and polymer matrix are established by DSC and XPS analyses. The ZIF loading could be achieved up to 40% without hampering the stability of the resulting MMMs. These membranes were evaluated for pure gas permeability, specifically aiming at C3H6/C3H8 separation, a highly desired application in industry. The ZIF-PPO hybrids display promising pure gas as well as mixed gas permeation performance. The 40% ZIF-8 and ZIF-67 loaded membrane display promising C3H6/C3H8 selectivity of 27.5 and 25, with a permeability of 12 and 13 barrer, respectively. The enhanced selectivity is attributed to the absence of defects eliminated due to metal-polymer interactions. The permeation study of a 30% ZIF-8 loaded membrane while varying transmembrane pressure and long-time exposure (150 h) of propylene at 60 psi indicated the excellent stability of the membrane. The sorption analysis further confirmed the molecular sieving characteristics of the ZIF@PPO MMMs. The mixed gas permeation performance showed promising results of high permeability as well as maintaining selectivity over a wide range of compositions.
Keywords: Interfacial interactions; Mixed matrix membrane; Olefin-paraffin separation; poly(phenyleneoxide); Zeolitic imidazole framework

ABPBI-based hollow fiber membranes for forward osmosis (FO) possessing low reverse salt flux - Thorat, Nitin M.; Lele, Ashish K.; Kharul, Ulhas K. (Desalination and Water Treatment, 2024)
The poly(2,5-Benzimidazole), known for its excellent thermochemical stability, was evaluated as a membrane material for forward osmosis. The dope in methane sulfonic acid was used to make hollow fiber membranes. The availability of bound MSA in HFMs was compared with its neutral form. Aqueous solutions of two common salts reported for FO (NaCl and MgCl2) were used as a draw solution at varying concentrations. The performance was determined in terms of water flux and reverse salt flux. The long-term performance of the membrane was assessed. The heat pretreatment of membranes was beneficial in offering low reverse salt flux, a crucial parameter in FO. The heat treatment at 350 degrees C exhibited excellent performance of low-RSF, irrespective of the draw solute used. The presence of MSA in the membrane matrix was found to be beneficial. Present HFMs exhibited reverse salt flux as low as 0.003 mol m-2 h-1 using 2 mol L-1 MgCl2 as a draw solution. The water flux of present membranes was lower than that of reported FO-membranes, which is attributable to the larger thickness of the present membranes. The findings will be used to make ABPBI-based membranes in thin form to elevate the fluxes and their practical applicability.
Keywords: ABPBI; Forward osmosis; Hollow fiber membrane; Low reverse salt flux

Chemodialysis of organic acids using ABPBI-based hollow fiber membranes - Gawas, Saroj; Alladi, Lavanya; Kharul, Ulhas K. (Journal of Membrane Science, 2024)
Organic acids are a class of essential commodity chemicals used in various industries. Their production methods are shifting from conventional chemicals to fermentation, driven by green process strategies, environmental regulations, cost feasibility, etc. Separating formed acid from the fermentation broth is a primary technological barrier. Conventional methods are complex and impose environmental issues. A promising approach, `Chemodialysis,' capable of transforming the techno-economical feasibility of acid recovery scenario by reducing the number of steps, needs further investigation. This work evaluates scalable hollow fiber membranes based on poly(2,5-benzimidazole) (ABPBI) for chemically assisted dialysis, viz., Chemodialysis. Sorption analyses of commercially significant organic acids (acetic, lactic, and glycolic acid) and nonacidic solutes (NaCl and glucose) were performed using conventional flat sheet samples to assess their role in governing permeation characteristics. The transport properties of acids in the presence of NaCl and glucose as co-solutes were analyzed using hollow fiber membranes. The high selectivity of acid over nonacidic solutes ranges from 400-22,400, coupled with high acid permeability, enhances the applicability of Chemodialysis for the separation of acids using hollow fiber membranes. The fluxes of acids (acetic, glycolic, and lactic) through dense, similar to 100 mu m thick, scalable hollow fiber membranes ranging from 10.9 to 13.12 g/m(2)h are highly appreciable.
Keywords: 5-benzimidazole); Acid separation; Chemodialysis; Hollow fiber membranes; Organic acids; Poly(2

Scalable, interfacially synthesized, covalent-organic framework (COF)-based thin-film composite (TFC) hollow fiber membranes for organic solvent nanofiltration (OSN) - Kunjattu, Shebeeb H.; Thorat, Nitin M.; Gawas, Saroj; Kharul, Ulhas K. (ACS Applied Materials and Interfaces, 2024)
Covalent organic frameworks have great potential for energy-efficient molecular sieving-based separation. However, it remains challenging to implement COFs as an alternative membrane material due to the lack of a scalable and cost-effective fabrication mechanism. This work depicts a new method for fabricating a scalable in situ COF hollow fiber (HF) membrane by an interfacial polymerization (IP) approach at room temperature. The 2D COF film was constructed on a polyacrylonitrile HF substrate using aldehyde (1,3,5-trimethylphloroglucinol, Tp) and amine (4,4 `-azodianiline (Azo) and 4,4 `,4 `'-(1,3,5-triazine- 2,4,6-triyl) trianiline (Tta)) as precursors. The COF membrane on the PAN substrate showed 99% rejection of Direct red-80 with remarkable solvent permeance. The rejection analysis revealed that the structural aspects of the solute molecule play a major role in rejection rather than the molecular weight. We further optimized the precursor concentrations to improve the permeation performance of the resulting membrane. The durability study reveals excellent stability of the membrane toward organic solvents. This study also demonstrated the easy scalability of the membrane fabrication approach. The approach was further extrapolated to fabricate a cation-based COF membrane. These charged membranes exhibited an enhanced rejection performance. Finally, this approach can facilitate industrially challenging molecular sieving applications using COF-based membranes.
Keywords: covalent-organic framework; hollow fiber; interfacial polymerization; organic solvent nanofiltration; selective COF membrane

Poly(2,5-Benzimidazole) as a membrane material for solvent dehydration: effect of bound methanesulfonic acid - Alladi, Lavanya; Lele, Ashish K.; Kharul, Ulhas K. (Journal of Applied Polymer Science, 2025)
Towards addressing issues of solvent stability of polymeric membrane materials for pervaporation (PV), this work investigates thermochemically robust poly(2,5-benzimidazole) (ABPBI) bound with methane sulfonic acid (MSA) for solvent dehydration, for the first time to our knowledge. Phase inversion membranes with and without bound-MSA were prepared, thermally treated at different temperatures up to 350 degrees C, and analyzed for physical and pervaporation properties. The physical characterizations (FTIR, WAXD, TGA, XPS, SEM, and EDX) and sorption analysis were performed using flat sheet membranes, whereas hollow fiber membranes were used for the pervaporation analysis with chosen solvents (alcohols and two polar aprotic solvents). Physical characterizations established the presence of MSA and the nonporous, dense nature of membranes, irrespective of their treatment temperatures. The sorption of pure solvents in the membrane is primarily affected by thermal treatment of the membranes. The pervaporation analysis was performed using different solvent: Water feed compositions. Using 85:15 as the feed, the average separation factors for dehydration of isopropanol, acetonitrile, and N,N-dimethylformamide (DMF) were 393, 213, and 185, respectively, with an appreciable ``pervaporation separation index.'' The long-term membrane performance till 360 h was analyzed to shed light on practical applicability.
Keywords: membranes; separation techniques; synthesis and processing techniques

Understanding the structural characteristics of modified ceramic hollow fiber oxygen transport membranes through in silico tomography simulation study - Jogdand, Shunottara M.; Sharma, Jyoti; Khilari, Rushikesh S.; Mahajan, Digvijay P.; Patil, Prashant; Pol, Harshavardhan V.; Torris, Arun; Agrawal, Ravi; Kharul, Ulhas K.; Devi, R. Nandini (ACS Applied Materials & Interfaces, 2025)
Design and development of integrated membrane reactor systems are gaining attention as a sustainable solution capable of performing multiple functions in a single reactor. Membrane reactors made of mixed ionic-electronic conduction materials dosing pure O to the reactions can be exploited for various catalytic processes. In this case, micro- and macrostructures of the membrane surface play a significant role in the permeation performance of membranes, and understanding these parameters prior to scaling up to modules is imperative. Here, 3D X-ray tomography imaging, a versatile nondestructive instrumental technique, is used in understanding the structural behavior of the membrane walls at different structural alignments, leading to anticipation of fouling areas upon assembling membrane reactors. La0.6Sr0.4Co0.2Fe0.8O3-delta hollow fiber membranes are fabricated by the phase inversion method and further modified by the optimized acid etching technique. In silico simulations on different morphologies before and after surface modifications are carried out under varying flow rates at nonambient temperatures to mimic real experimental conditions. Critical parameters such as gas velocity, pressure exerted on cavity walls, and strain, dictating structural integrity of the fibers under experimental conditions, were evaluated. As a result of the assessment, the surface-modified structural morphology with finger-like cavities initiating from the inner wall of the membrane was found to be robust. Increase in the pore size, nonuniform pore size distribution, and irregular and interdigitated cavities formed in outer fingered membranes after multiple surface treatments led to an similar to 5 fold increase in the average pressure exerted at the cavity walls when compared to inner fingered membranes. Strain profile generated for inner fingered membranes shows homogeneous distribution of strain for the applied stress throughout the 3D geometry of the membrane. This detailed structural analysis of the membrane will help in building a more robust and efficient system for scale-up applications.
Keywords: 3D X-ray tomography; in silico simulation; oxygen transport membranes; perovskite; phase inversionmethod

Poly(2,5-Benzimidazole)-based flat sheet membranes: investigating effects of dope solvent and membrane heat treatment on forward osmosis and acid enrichment performances - Somkuwar, Nitin C.; Thorat, Nitin M.; Ambade, Ashootosh; Kharul, Ulhas K. (Journal of Applied Polymer Science, 2026)
The present work investigates two methods for preparing defect-free, symmetric membranes of the thermochemically robust polymer, poly(2,5-benzimidazole) (commonly known as ABPBI) for forward osmosis (FO), a growing technology for niche separations. The obtained polymer and membranes were analyzed for physical properties of significance. The FO analysis was performed using three salt solutions, viz., sodium chloride (NaCl), magnesium chloride (MgCl2), and sodium sulfate (Na2SO4). The effects of casting methodology (solvents present in the dope), membrane heat treatment, draw solution concentration, long-duration analysis, and FO-assisted enrichment of organic acids were evaluated. Some of the membranes exhibited extremely low reverse salt flux (RSF), which conveys the novelty of these membranes. Some of these membranes were analyzed using a high draw solution (DS) concentration (4 mol L-1) to enhance water flux and further employed to enrich organic acids. The aqueous acetic and methacrylic acid concentrations were enriched from 4.89 and 2.93 mol L-1 to 11.88 and 10.01 mol L-1, respectively. These results demonstrate an unmet need of concentrating methacrylic acid (a temperature-sensitive compound possessing a double bond). The present work demonstrates the potentials of ABPBI-based symmetric, thin membranes for FO and their industrial applicability for the first time.
Keywords: Applications; membranes; separation techniques